Предмет: Алгебра,
автор: kolobok2000
Ответы
Автор ответа:
0
Х^3 - 3х^2 - 4х + 12 = 0
Х^2( Х - 3 ) - 4( Х - 3 ) = 0
( х^2 - 4 )( Х - 3 ) = 0
( Х - 2 )( Х + 2 )( Х - 3 ) = 0
Х - 2 = 0
Х = 2
Х + 2 = 0
Х = - 2
Х - 3 = 0
Х = 3
Ответ ( - 2 ) ; 2 ; 3
Х^2( Х - 3 ) - 4( Х - 3 ) = 0
( х^2 - 4 )( Х - 3 ) = 0
( Х - 2 )( Х + 2 )( Х - 3 ) = 0
Х - 2 = 0
Х = 2
Х + 2 = 0
Х = - 2
Х - 3 = 0
Х = 3
Ответ ( - 2 ) ; 2 ; 3
Похожие вопросы
Предмет: Математика,
автор: noname5265
Предмет: Математика,
автор: ajlananazenova
Предмет: Другие предметы,
автор: anasnursat
Предмет: Математика,
автор: Аноним
Предмет: Обществознание,
автор: mbegoevmailru